2021
DOI: 10.22541/au.161132817.77514172/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pteridine pigments compensate for environmental availability of carotenoids

Abstract: Carotenoid-based colours are a textbook example of honest signalling because carotenoids must be acquired from the environment. However, many species produce similar colours using self-synthesised pteridine pigments. A compelling but untested hypothesis is that pteridines compensate for low environmental availability of carotenoids because it is metabolically cheaper to synthesise pteridines than to acquire and sequester carotenoids. Based on a phylogenetic comparative analysis of 11 pigment concentrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Meanwhile, pigment-rich dewlap skin upregulated and differentially expressed genes from both the pteridine carotenoid pathways. Although chromatographic studies of anole skin previously suggested that orange and yellow coloration result primarily from pteridines ( Ortiz and Williams-Ashman 1963 ; Steffen and McGraw 2007 ), the upregulation of both the pteridine and carotenoid pathways in orange tissue relative to yellow and white tissues supports recent transcriptomic and chromatographic that indicated that both carotenoids and pteridines can be involved in the production of orange and red colors in squamates ( McLean et al 2017 , 2019 ; Stuart-Fox et al 2021 ). Accordingly, orange skin upregulated genes previously linked to the regulation of carotenoid intake from the bloodstream in mice ( BCO1, SCARB1 , ADH1B ; Widjaja-Adhi et al 2015 ), genes from the CYP family of monooxygenases that ketolate xanthophylls in birds ( Toews et al 2017 ), and genes responsible for the development and maintenance of melanophores and erytrhophores/xanthohores in zebrafish ( CSF1R , KIT , KITLG ; Patterson and Parichy 2019 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Meanwhile, pigment-rich dewlap skin upregulated and differentially expressed genes from both the pteridine carotenoid pathways. Although chromatographic studies of anole skin previously suggested that orange and yellow coloration result primarily from pteridines ( Ortiz and Williams-Ashman 1963 ; Steffen and McGraw 2007 ), the upregulation of both the pteridine and carotenoid pathways in orange tissue relative to yellow and white tissues supports recent transcriptomic and chromatographic that indicated that both carotenoids and pteridines can be involved in the production of orange and red colors in squamates ( McLean et al 2017 , 2019 ; Stuart-Fox et al 2021 ). Accordingly, orange skin upregulated genes previously linked to the regulation of carotenoid intake from the bloodstream in mice ( BCO1, SCARB1 , ADH1B ; Widjaja-Adhi et al 2015 ), genes from the CYP family of monooxygenases that ketolate xanthophylls in birds ( Toews et al 2017 ), and genes responsible for the development and maintenance of melanophores and erytrhophores/xanthohores in zebrafish ( CSF1R , KIT , KITLG ; Patterson and Parichy 2019 ).…”
Section: Discussionmentioning
confidence: 77%
“…The enzyme responsible for ketolation in birds and turtles (which encompass archosaurs, the sister clade of lepidosaurs [tuataras + squamates]), was recently identified as CYP2J19 , a gene that is not present in the anole genome ( Lopes et al 2016 ; Mundy et al 2016 ; Twyman et al 2016 ). Given that CYP is used to ketolate carotenoids in taxa as divergent as anurans and birds, and that archosaurs use CYP2J19 to perform this task, the process of ketolation implied by transcriptomic and chromatographic studies in Australian Lizards ( McLean et al 2017 ; McLean et al 2019 ; Stuart-Fox et al 2021 ) as well as our own is likely performed by another enzyme in the CYP family.…”
Section: Resultsmentioning
confidence: 95%
“…[33] Stuart-Fox found a correlation between the concentration of these pteridines and skin color saturation in lizards, suggesting that the "colorless pteridines may contribute to skin color due to their crystallinity rather than spectral absorption". [34] Pteridine pigment granules (pterinosomes) are often identified in TEM by their unique cross-sectional texture, exhibiting concentric lamellae of membranes -resembling an onion (Figure 4a). [35] However, this onion-like morphology is not a general feature of all pteridines and is associated specifically with the yellow/brown/red unconjugated pteridines (e. g., sepiapterin, drosopterin, neopterin, Figure 2) which are functionalized at position 6 of the pteridine ring.…”
Section: Pteridinesmentioning
confidence: 99%